The Influence of Mass Media on the Modern Japanese Language - Anistratenko, Lidia; Asadchykh, Oksana; Bukriienko, Andrii; Komarnytska, Tamara; Komisarov, Kostiantyn (Jurnal Arbitrer, 2024)
The purpose of this study is to examine the key influence of mass media on different language levels based on analysing several modern newspapers and magazines published in Japan. The article uses the following methods of analysis: structural analysis, lexical and semantic analysis, stylistic analysis, analytical and synthetic method, and contextual analysis. The results of the study showed that the most noticeable influence of mass media on the modern Japanese language was observed at the lexical and stylistic levels and less noticeable – at the phonetic, word-forming, morphological, and syntactic levels. Phonetic changes in the Japanese press were associated with the adaptation of non-equivalent vocabulary from European languages using the Japanese alphabet (katakana). At the word-forming level, the changes concerned primarily uncharacteristic derivational units that came to Japanese from English, and at the morphological level, the influence was conducted mainly through the demonstration of samples of the correct use of case endings, tenses and coordination of parts of speech. At the syntactic level, there was a variety of syntactic constructions, in particular, to expand the content, introduce additional sentences, and change the topic of conversation. The stylistic influence of mass media on the Japanese language system consisted in the use of artistic tropes and stylistic figures, in particular, metaphors, hyperbole, and periphery, which can be considered patterns for communicative behaviour.